Retorno do investimento em marketing por empresas de telefonia móvel: uma avaliação das operadoras do estado de São Paulo - Sublaban, Cleusa Satico Yamamoto (2006)
This study proposes an adaptation to the mobile telephone sector of the Rust Lemon & Zeithaml (2004) model of marketing investment. The model provides a method for the evaluation of investments in strategic marketing areas (value, brand and relationship equity). Applied to São Paulo State cellular telephone companies (Vivo, Claro and TIM), the model allows the estimation of a customer probability of change from the present operator to a competitor; and the assessment of a marketing initiative contribution, verifying if it exceeds its cost of capital. Finally, through the application of model, an estimate of customer equity is calculated for the three studied cellular telephone operators.